2021
DOI: 10.26418/lkuntan.v4i3.48095
|View full text |Cite
|
Sign up to set email alerts
|

Struktur Komunitas Makrozoobentos di Pantai Gosong Kabupaten Bengkayang Kalimantan Barat

Abstract: Pantai merupakan zona yang umum yang salah satunya dijadikan tempat wisata oleh masyarakat/wisatawan setempat serta menjadi habitat berbagai organisme. Adanya aktivitas masyarakat di sekitar Pantai Gosong beresiko mempengaruhi ekosistem biota yang hidup di kawasan tersebut, salah satunya makrozoobentos. Penelitian ini bertujuan untuk mengetahui struktur komunitas makrozoobentos di Pantai Gosong, Kecamatan Sungai Raya Kepulauan, Kabupaten Bengkayang. Penelitian ini telah dilakukan pada Bulan November - April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
5

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
4
1
5
Order By: Relevance
“…These results indicate that the condition macrozoobentos diversity on Poncan Gadang Island in the moderate category. Moderate diversity indicates that environmental conditions waters are quite supportive for macrozoobentos life and ecosystems seagrass in such locations has sufficient productivity, ecosystem conditions are sufficient balanced and moderate ecological pressure (Herawati et al, 2017;Machrizal et al, 2020;Siahaan et al, 2021;Wijana et al, 2019). The results of the analysis of the dominance index at 5 research stations showed the value of close to 0, this indicates that on Poncan Gadang Island there is no one of the predominate types of macrozobentos (found in numbers a lot).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that the condition macrozoobentos diversity on Poncan Gadang Island in the moderate category. Moderate diversity indicates that environmental conditions waters are quite supportive for macrozoobentos life and ecosystems seagrass in such locations has sufficient productivity, ecosystem conditions are sufficient balanced and moderate ecological pressure (Herawati et al, 2017;Machrizal et al, 2020;Siahaan et al, 2021;Wijana et al, 2019). The results of the analysis of the dominance index at 5 research stations showed the value of close to 0, this indicates that on Poncan Gadang Island there is no one of the predominate types of macrozobentos (found in numbers a lot).…”
Section: Resultsmentioning
confidence: 99%
“…Macrozoobentos are communities of organisms that live based on bottom or sediments in an aquatic habitat. They have a relatively fixed and very limited living habitat, therefore they are more susceptible to environmental disturbances such as changes in water quality and sediments, but are very well used as biological indicators determining conditions in the aquatic ecosystem (Bai'un et al, 2021;Saputri et al, 2021;Siahaan et al, 2021). Macrozoobenthos are a group of organisms that are often found alive associated with seagrass beds ecosystem (Machrizal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Makrozoobentos gastropoda dan bivalvia dominan pada perairan ini (Pramika et al, 2021). Makrozoobentos yang ditemukan di Pantai Gosong, Bengkayang, Kalimantan Barat lebih sedikit, hanya 3 kelas (Bivalvia, Gastropoda dan Holothuroidea) (Siahaan et al, 2021).…”
Section: Komposisi Dan Kepadatan Makrozoobentosunclassified
“…Barus (2004) menyatakan bahwa indeks keanekaragaman menunjukkan jumlah spesies dan persebaran individu. Indeks keanekaragaman makrozoobentos di Pantai Gosong, Bengkayang, Kalimantan Barat adalah 0,72-1,5 dengan kategori rendah hingga sedang (Siahaan et al, 2021). Nilai indeks keanekaragaman sedang, menunjukkan jenis spesies yang beragam dan cenderung labil (Widhiandari et al, 2021).…”
Section: Indeks Keanekaragaman Indeks Keseragaman Indeks Dominansiunclassified
See 1 more Smart Citation